The effectiveness of serve in tennis depending on the placement of palm across the racket grip inwards or outwards - Mavvidis, A.; Manousaridou, A.; Grivas, N.; Evagelidis, T.; Laios, A (Journal of Physical Education and Sport, 2014)
The purpose of this study was to investigate the accuracy and speed of serve in tennis depending on the placement of palm across the racket grip inwards or outwards. Apart from the personal grip two additional kinds of grip were examined, one with the wrist two cm "inwards" and a second with two cm "outwards", from the tip of the handle of the racket. The research sample consisted of 31 tennis players, 16 advanced and 15 intermediate, aged 23±3,4 years old. The players performed 10 serves with each one of the three types of grip, aiming to achieve both valid and high speed serves. The measurement of speed was achieved with the use of a radar gun. Differences in the performance were tested using ANOVA analysis, while differences in speed of valid and invalid services among the three kinds of grips were tested using the Wilcoxon Test. The results indicated statistically significant differences between the two genders (P<.001). The differences among the grips were also statistically significant (P<.05). The advanced players showed better results using their personal grip. However the intermediate players using the "inconvenient" wrist position 2 cm "outwards" the handle, showed better results regarding the speed of serve and especially the speed of invalid serves (P<.05). The use of this type of grip without firmness produced serves of higher speed, probably due to the freedom in wrist and the longer lever that it offers. The current research reveals that when an intermediate player wants to change the serve technique, in order to achieve higher speed in serve, a change to position 2cm "outwards" off the handle would probably provide better results, but it should be combined with more training for high accuracy achievement